VARIASI KARAKTER KUANTITATIF KEPITING Uca annulipes (BRACHYURA: OCYPODIDAE) di KEPULAUAN INDONESIA - Murniati, Dewi Citra (BIO-SITE |BIOLOGI Sains Terapan, 2015)
Uca annulipes are deposit feeder crab which is widely distributed in Indonesian mangrove areas. The systematic study of the species completely based on the qualitative character without the quantitative one. This study describes the variation in quantitative characters of U. annulipes from different locations in Indonesia. Descriptive method with univariate and multivariate analyses based on quantitative character ratio was used in this study. The univariate analysis showed that the highest value of either the quantitative character or quantitative character ratio was found from the western Indonesian population.Â Meanwhile, the multivariate analysis showed that U. annulipes from western Indonesia, Sulawesi, and Nusa Tenggara have a discrete cluster.